Backyards life - Matsheng, Chelsy (School of Architecture and Planning, University of the Witwatersrand., 2017)
The RDP housing programme was considered as a solution to poverty in South Africa. It was believed that households could either sell their house in the housing market or use it as a collateral to access finance. However, this has proven ineffective because households often attach values to their housing, and are not willing to either sell or use their houses as collateral. Households rather resort to generating income for themselves through backyard rental accommodation. However the state been unsupportive of the backyard rental accommodation, reasoning that it increases the density of the houses beyond which it was created for. The findings of this research reveals that the income from the backyard rental accommodation income plays an important role in improving the quality of life of the RDP beneficiaries. This research argues that backyard rental accommodation provides the RDP beneficiaries with opportunities to improve their economic situation, material and social well-being and also allows them to improve their houses, thereby improving their quality of life. At the same time providing affordable, flexible accommodation and social stable environments to tenants. Taking into consideration of the benefits of backyard rental accommodation to RDP beneficiaries, this research argues it helps housing to perform as an asset. This is because it does not only provide survival strategy to RDP beneficiaries, it helps them improve their economic situation and consequently improves their quality of life.
Life of the backyards:evaluating backyard rental landlords’ and tenants’ quality of life of landlords in RDP settlements - the case of Diepsloot
I declare that this research report is my own work. It is being submitted as a requirement for the Bachelor of Sciences (Honours) in Urban and Regional Planning degree at the University of the Witwatersrand, Johannesburg. It has not been submitted before for any degree or examination at any other University.
Keywords: Reconstruction and development programme (RDP); Backyard rental accommodation; Life improvement--Quality; Affordable accommodation